BIOMECHANICAL PROPERTIES AND MACROELEMENT ELEMENT COMPOSITION OF LONG TUBULAR BONE OF RATS UNDER EXPERIMENTAL HYPERGLYCAEMIA - Ponyrko, A.O.; Dmytruk, S.M.; Bumeister, V.I. (World of Medicine and Biology, 2021)
The pathomorphological basis for the development of diabetic disorders in various bones is a relevant subject of modern experimental research on the modeling of diabetes–associated destructive processes in the skeletal system. They are characterized by reduced bone density, which leads to an increased risk of fractures. Bone strength mainly depends on the interaction and concentration of chemical elements such as Ca, P, Mg, and K. Therefore, the purpose of our study was to determine the interdependence of changes in biomechanical parameters depending on the concentration of chemical elements in long tubular bones of rats under chronic hyperglycemia. The study was performed on 72 adult white laboratory rats lasting 180 days. It was found that starting from 30 days of uncontrolled chronic hyperglycemia, the bone mineral density in rats of the experimental group gradually decreased in comparison with the dynamics of the corresponding indexs in animals of the control group. These changes were accompanied by pronounced demineralization of both bones, as evidenced by significant losses of macronutrients (Ca, P, Mg and K). As a result, in chronic hyperglycemia gradually formed a complex violation of the structure and biomechanical properties of long tubular bones, which is a pathomorphological basis in the corresponding loci of the skeletal system.